Covid-19 and Children with Immune Thrombocytopenia: emerging issues - Giuseppe Lassandro; Valentina Palladino; Viviana Palmieri; Anna Amoruso; Giovanni Del Vecchio; Paola Giordano (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
Letter to Editor